Deterministic and stochastic models of automotive engine fuelled with palm biodiesel - Azuwir, Mohd Noor; Mohd Zaki, Abdulmuin, Prof. Dr.; Abdul Hamid, Adom, Prof. Madya Dr. (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Perlis, Malaysia.